The effects of steam injection on the performance and emission parameters of a Miller cycle diesel engine - Gonca, Guyen; Sahin, Bahri; Parlak, Adnan; Ust, Yasin; Ayhan, Vezir; Cesur, Idris; Boru, Baris (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The application of the Miller cycle into the internal combustion engines is proposed to decrease NOx emissions, in the recent years. Another NOx control technique is the steam injection method (SIM). In this study, the application of these methods together into a single cylinder, direct injection diesel engine is experimentally and theoretically performed. Two different Miller cycles, which provide 5 and 10 crank angle (CA) retarding compared to standard condition, are applied with two different camshafts. SIM is applied at three different injection rates which are 10%, 20% and 30% of the fuel mass. The results obtained are compared with standard conditions in terms of the performance and emissions. The simulation results are verified with experimental data with non-notable errors. In the experimental results, NO and CO2 emissions decreased up to 48% and 2.2%; HC and CO emissions increased by 46% and 34% with the penalty by 6.4% and 9.2% for the effective power and efficiency. The optimum condition has been defined as 10 CA retarding and 30% steam injection rate (C62-S30) in terms of the maximum NO reduction. The results demonstrate that the combination can be applied into the diesel engines to minimize NO and CO2 emissions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Diesel engine; Steam injection method; Miller cycle; Engine performance; NOx emissions; Two-zone combustion model; REDUCE NOX EMISSIONS; HEAT-ENGINE; EFFICIENCY; Thermodynamics; Energy & Fuels